CLOUD COMPUTING: A technology for Communication (International Journal of Engineering and Computer Science, 2017)
is paper illustrate about cloud computing. Cloud computing is the use of computing resources (hardware and software) that are delivered as a service over a networks (typically the Internet). The name comes from the use of a cloud-shaped symbol as an abstraction for the complex infrastructure it contains in system diagrams. Cloud computing entrusts remote services with a user's data, software and computation. Cloud computing relies on sharing of resources to achieve coherence and economies of scale similar to a utility (like the electricity grid) over a network.At the foundation of cloud computing is the broader concept of converged infrastructure and shared services.